Financial development policy and growth / Jean-Claude Berthélemy ,Aristomène Varoudakis. - Berthélemy, Jean-Claude (velopment centre of the Organisation for economic co-operation and development, 1996)
A growing body of theoretical and empirical work would push even skeptics toward the belief that the development of financial markets and institutions is critical to economic growth, rather than a sideshow or a passive response to growth.